Prevalence of bulimic behavior and associated factors in undergraduate female students (Archives of Clinical Psychiatry, 2009)
CONTEXT: Bulimia nervosa is characterized by repetitive binge eating episodes followed by inadequate compensatory behaviors. Prevalence in teenager girls and young women is about 1% to 3%. OBJECTIVE: To estimate the prevalence of bulimic behavior and associated factors for first year undergraduate women. METHODS: A systematic random sample (n = 220) was analyzed and the bulimic investigatory test Edinburgh (BITE) criteria was used to evaluate bulimia nervosa behaviors. Satisfaction with body image and nutritional status were also analyzed. Factors associated to bulimic behavior (BITE >; 15) were analyzed by non-conditional multiple logistic regression. RESULTS: The response rate in the present study was 98.7%. The prevalence of bulimia nervosa symptoms was 3.6% (95% CI 1.1; 6.1), and the prevalence of non-satisfaction with body image was 20% (95% CI 14.7; 25.3). Undergraduate students unsatisfied with their own body image had 15.4 times more chances of developing bulimia nervosa behaviors than those who were satisfied with their own body images, independently of the other variables analyzed. CONCLUSION: Satisfaction with body image was the most important factor associated with bulimia nervosa behavior.